PERKEMBANGAN HUKUM ASURANSI DALAM PRANATA HUKUM NASIONAL - Dani, Sapuan (MAJALAH KEADILAN, 2021)
Insurance or coverage is one of the basic human needs, namely the need for a sense of security and protection against the possibility of suffering a loss, with insurance ensuring the fulfillment of the certainty of the need for protection, this causes insurance to grow and develop continuously, in accordance with the development of needs. human beings that are in line with and in line with the level of development of civilization so as to arrive at a certain level of economic progress needed by humans. Whereas the insurance business in Indonesia has been running side by side with other activity sectors for a long time, the insurance arrangement is only based on the provisions in the KUHD, which regulates insurance as an agreement, on the other hand the insurance business is a promising business sector to the insured and at the same time this fund involves funds Public. With the rapid development of technology and economic development, the need for strong and reliable insurance is increasingly felt.